Function of the Letter (YA) in Persian and Arabic Languages - Ismati , Sayyid Azimullah; Latifpoor, Lutfullah (Journal of Social Sciences - Kabul University, 2020)
Syntax plays a fundamental role in shaping the structure and meaning of sentences in both Arabic and Persian languages. The letter (YA) holds a significant grammatical function in both languages, contributing to sentence construction and enhancing the beauty of speech, particularly in literary texts, including poetry and prose. Analyzing words and sentences from a syntactic and morphological perspective reveals the crucial role of (YA) in both languages. Despite their similarities, Arabic and Persian exhibit notable differences in the usage and function of this letter. This study explores the various types and functions of (YA) in Arabic and Persian through a comparative approach, employing the library research method to highlight its grammatical importance and linguistic variations.